Phase, hardness, and deformation slip behavior in mixed HfxTa1-xC. (15th February 2018) - Smith, Chase J.; Yu, Xiao-Xiang; Guo, Qianying; Weinberger, Christopher R.; Thompson, Gregory B.
Abstract: A series of Hfx Ta1-x C atomic compositions, where x = 0.0, 0.13, 0.25, 0.50, 0.75, 0.83, and 1.0, were computationally and experimentally studied in terms of their phase, hardness, and dislocation emission behavior. Using an ab initio evolutionary algorithm, the B1 rocksalt structure was found to be the 0 K ground state phase for the binary carbides whereas the ternary compounds were a mixture of metal-site ordered monoclinic, trigonal, and cubic structures. However, all experimental carbides were found to exhibit a B1 structure, with two B1 phases forming for Hf-rich ternary compositions. A modest rise in the elastic constant computationally predicted hardness was found with experimental mean values showing a similar trend from nanoindentation tests. With the presence of Ta, even in small amounts, in the Hf-rich ternary compositions, <110>{111} slip was observed which is a change from the reported <110>{110} slip for HfC. This change is explained by the promotion of an intrinsic stacking fault in the {111} planes. Graphical abstract: Image 1